2017
DOI: 10.1111/jvim.14857
|View full text |Cite
|
Sign up to set email alerts
|

Immune Function in Critically Ill Dogs

Abstract: BackgroundPeople with critical illness (CI) commonly develop various forms of immune dysfunction, however, there is limited information concerning immune dysfunction in dogs with CI.HypothesisThe immune response in CI dogs differs from that of healthy dogs.AnimalsImmunologic variables were compared between 14 dogs with CI, defined as APPLEfast score of >20 points, admitted to the University of Missouri Veterinary Health Center Small Animal Clinic Intensive Care Unit and healthy controls (n = 15).MethodsCohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In dogs, 2 similar studies, one conducted in critically ill dogs 23 and the other in septic dogs, 47 also found a decrease in oxidative burst activity when phagocytes were stimulated by PMA and immune complexes, respectively. One study postulated that in canine critical illness, dysfunction in the protein kinase C (PKC) signaling pathway may be the reason for decreased oxidative burst activity.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In dogs, 2 similar studies, one conducted in critically ill dogs 23 and the other in septic dogs, 47 also found a decrease in oxidative burst activity when phagocytes were stimulated by PMA and immune complexes, respectively. One study postulated that in canine critical illness, dysfunction in the protein kinase C (PKC) signaling pathway may be the reason for decreased oxidative burst activity.…”
Section: Discussionmentioning
confidence: 83%
“…Oxidative burst and phagocytic activities were determined using commercial kits (Phagoburst and Phagotest kits, respectively; Glycotope Biotechnology). Both kits have been used successfully in previous canine studies 23,30,33 and were used according to the manufacturer’s instructions. Briefly, oxidative burst activity was determined by incubating 2 samples of 100 µL of precooled (0°C) heparinized whole blood, one with opsonized Escherichia coli bacteria and one with phorbol-12-myristate 13-acetate (PMA), at 37°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on neutrophil function in B. bovis reported that neutrophils displayed increased phagocytic activity, but reduced respiratory burst during peak parasitemias (24). Moreover, studies that investigated the immune function in septic and critically ill dogs, reported that neutrophil function was impaired, possibly due to dysfunction in the NADPH oxidase complex, which is the enzyme tasked with catalyzing one of the initial reactions in the respiratory burst complex (25,26). A concept called sepsis-induced immunosuppression or immunoparalysis, similar to what has been reported in humans, was used to describe this phenomenon and imparts a negative prognosis on affected animals (25).…”
Section: Discussionmentioning
confidence: 99%